55th AIAA/ASME/ASCE/AHS/ASC Structures, Structural Dynamics, and Materials Conference 2014
DOI: 10.2514/6.2014-0344
|View full text |Cite
|
Sign up to set email alerts
|

Aeroelastic Tailoring of a Plate Wing with Functionally Graded Materials

Abstract: This work explores the use of functionally graded materials for the aeroelastic tailoring of a metallic cantilevered plate-like wing. Pareto trade-off curves between dynamic stability (flutter) and static aeroelastic stresses are obtained for a variety of grading strategies. A key comparison is between the effectiveness of material grading, geometric grading (i.e., plate thickness variations), and using both simultaneously. The introduction of material grading does, in some cases, improve the aeroelastic perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The common subjects that use ToCs to facilitate solutions of multi-objective optimisation problems are Manufacturing networks optimisation (Bitran and Morabito, 1999), scheduling (Catalão et al , 2008), capacity planning and resource allocation (Bretthauer et al , 2003) and inventory management (Grewal et al , 2014). The highlighted roles of ToCs within these studies are Decision support (Holtzman, 1984; Preetha Roselyn et al , 2014), data representation and visualisation (Abido, 2003; Rhyu and Kwak, 1988), best solution compromise (Avigad and Moshaiov, 2010; Mohagheghi et al , 2014; Zhao et al , 2011), comparing conflicting parameters (Dunning et al , 2014; Kuo et al , 2014), comparing solutions (Gardner and Everette, 1990; Quirante et al , 2013; Suwanruji and Enns, 2007) and feasible/infeasible area definition (Cao and Yang, 2004; Samarasinghe et al , 2013). However, these ToCs are developed by using the data generated by algorithms and mathematical calculations rather than real data, experience and knowledge.…”
Section: Review Of the Related Literaturementioning
confidence: 99%
“…The common subjects that use ToCs to facilitate solutions of multi-objective optimisation problems are Manufacturing networks optimisation (Bitran and Morabito, 1999), scheduling (Catalão et al , 2008), capacity planning and resource allocation (Bretthauer et al , 2003) and inventory management (Grewal et al , 2014). The highlighted roles of ToCs within these studies are Decision support (Holtzman, 1984; Preetha Roselyn et al , 2014), data representation and visualisation (Abido, 2003; Rhyu and Kwak, 1988), best solution compromise (Avigad and Moshaiov, 2010; Mohagheghi et al , 2014; Zhao et al , 2011), comparing conflicting parameters (Dunning et al , 2014; Kuo et al , 2014), comparing solutions (Gardner and Everette, 1990; Quirante et al , 2013; Suwanruji and Enns, 2007) and feasible/infeasible area definition (Cao and Yang, 2004; Samarasinghe et al , 2013). However, these ToCs are developed by using the data generated by algorithms and mathematical calculations rather than real data, experience and knowledge.…”
Section: Review Of the Related Literaturementioning
confidence: 99%
“…Niino and Maeda (1990) for example examined the use of FGMs for handling very high thermal gradients in space-planes and the associated thermal stresses. Dunning et al (2014) investigated FGMs for use in aircraft wings and found that being able to vary material properties along with the geometry beneted the aero-elastic performance. An overview of FGM optimisation can be found in Birman and Byrd (2007) along with an overview of the eld in general.…”
Section: Functionally Graded Materialsmentioning
confidence: 99%